2017
DOI: 10.14814/phy2.13370
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis and Inflammation: Exploring the effects of the components of E-cigarette vapor on macrophages

Abstract: E‐cigarettes are perceived as harmless; however, evidence of their safety is lacking. New data suggests E‐cigarettes discharge a range of compounds capable of physiological damage to users. We previously established that cigarette smoke caused defective alveolar macrophage phagocytosis. The present study compared the effect E‐cigarette of components; E‐liquid flavors, nicotine, vegetable glycerine, and propylene glycol on phagocytosis, proinflammatory cytokine secretion, and phagocytic recognition molecule exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
81
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 84 publications
(173 reference statements)
11
81
3
Order By: Relevance
“…The results found in literature, regarding the cytotoxicity of e-vapor extract flavored are contradictory; some studies have shown a cytotoxic effect when tobacco, cherry, cinnamon and coffee flavors were tested [32,[40][41][42]. However, in agreement with our results, Ween et al observed that cytotoxicity in THP-1 macrophages was not related with the e-cig flavor [26]. It has been suggested that cell line used, nicotine, flavors, PG/PV ratio, voltage and potency of the device can influence in the toxicity effects of e-vapor [43].…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…The results found in literature, regarding the cytotoxicity of e-vapor extract flavored are contradictory; some studies have shown a cytotoxic effect when tobacco, cherry, cinnamon and coffee flavors were tested [32,[40][41][42]. However, in agreement with our results, Ween et al observed that cytotoxicity in THP-1 macrophages was not related with the e-cig flavor [26]. It has been suggested that cell line used, nicotine, flavors, PG/PV ratio, voltage and potency of the device can influence in the toxicity effects of e-vapor [43].…”
Section: Discussionsupporting
confidence: 78%
“…Coffee flavor was chosen because of the toxic effect observed in fibroblasts [32]. 60 mL of evapor was extracted for 3 sec, after which a 30 sec break followed; the process was repeated 40 times (average of puffs found in literature), in 10 mL of RPMI medium or 7H9-tween [21,26]. The e-vapor extract was also sterilized using a 0.22 μm filter.…”
Section: Cigarette Smoke and E-vapor Extractionmentioning
confidence: 99%
See 3 more Smart Citations